Implementation of Learning Assessment in Islamic Religious Education at Madrasah Aliyah Negeri 3 Pekanbaru City - Widodo, Widodo; Firdaus, Firdaus; Sholeh, Ahmad; Alfaturrahman, Alfaturrahman; Tarigan, Target Muranaki (UIR Press, 2026)
This study aims to analyze the implementation of Islamic Religious Education (PAI) learning outcome assessment and the relationship between authentic assessment concepts and practice in the field. The study used a qualitative approach with a case study at Madrasah Aliyah Negeri 3 Pekanbaru City. Participants included PAI teachers, the principal, and students selected through purposive and snowball sampling techniques. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that assessment was still dominated by cognitive aspects through written tests, while affective and psychomotor assessments had not been implemented optimally and systematically. Time constraints, administrative burdens, and minimal training were the main inhibiting factors. These findings indicate a mismatch between authentic assessment concepts and learning practices. This study contributes to enriching studies on PAI learning evaluation and emphasizes the importance of strengthening teacher competencies and policy support. Further research is recommended to develop a more applicable and contextual authentic assessment model.